2020
DOI: 10.1007/s13632-020-00681-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Input on the Microstructural, Mechanical, and Corrosion Properties of Dissimilar Weldment of Conventional Austenitic Stainless Steel and Low-Nickel Stainless Steel

Abstract: In the present investigation, an attempt has been made to investigate the replacement compatibility of conventional austenitic stainless steel (316L) with low-Ni austenitic stainless steel (201) by employing their dissimilar welding using gas tungsten arc welding technique with varying heat input. The effects of heat input on the microstructural, mechanical, and corrosion properties were studied. The result depicts the balanced austenite/ferrite content in the fusion zone for both the heat inputs. The low heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…Furthermore, the fast cooling rate associated with the low heat input results in higher delta ferrite content promoted in the FZ. This also enhances the strength of the joint welded at low heat input, which is in agreement with the literature [13,33,38]. [40,41] and presented in Table 5.…”
Section: Joint Efficiency =supporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, the fast cooling rate associated with the low heat input results in higher delta ferrite content promoted in the FZ. This also enhances the strength of the joint welded at low heat input, which is in agreement with the literature [13,33,38]. [40,41] and presented in Table 5.…”
Section: Joint Efficiency =supporting
confidence: 92%
“…These results can be attributed to the high content of delta ferrite in the weld metal at the low heat input. In addition, the small dendrite sizes and interdendritic spacing in the weld metal enhance the tensile properties [13,27]. The joint efficiency was calculated according to Equation (5) [40,41] and presented in Table 5.…”
Section: Tension Test Resultsmentioning
confidence: 99%
“…The residual stresses in both phases were below the yield strength, whose values obtained by tensile test were 518±36 MPa and 287±9 MPa, respectively, for 201LN and 304L steels. The difference between these values was 3, which also contributed to an increase in the mechanical properties 36,37 .…”
Section: Resultsmentioning
confidence: 99%
“…Considerable efforts related to the welding of MMn–SSs have been made to investigate the effects of welding parameter changes in the metallurgical characteristics and mechanical properties of the welded joints. The effect of heat input manipulation on the characteristics of similar and dissimilar MMn–SS welded joints was reported in the literature [ 11 , 17 , 18 , 19 , 20 , 21 ]. It was found that with the increase in the heat input, the mechanical performance of the welded joints deteriorated.…”
Section: Introductionmentioning
confidence: 99%